Genome‐wide ancestry and introgression in a Zambian baboon hybrid zone. Issue 8 (16th March 2021) - Chiou, Kenneth L.; Bergey, Christina M.; Burrell, Andrew S.; Disotell, Todd R.; Rogers, Jeffrey; Jolly, Clifford J.; Phillips‐Conroy, Jane E.
Abstract: Hybridization in nature offers unique insights into the process of natural selection in incipient species and their hybrids. In order to evaluate the patterns and targets of selection, we examine a recently discovered baboon hybrid zone in the Kafue River Valley of Zambia, where Kinda baboons ( Papio kindae ) and grey‐footed chacma baboons ( P. ursinus griseipes ) coexist with hybridization. We genotyped baboons at 14, 962 variable genome‐wide autosomal markers using double‐digest RADseq. We compared ancestry patterns from this genome‐wide data set to previously reported ancestry from mitochondrial‐DNA and Y‐chromosome sources. We also fit a Bayesian genomic cline model to scan for genes with extreme patterns of introgression. We show that the Kinda baboon Y chromosome has penetrated the species boundary to a greater extent than either mitochondrial DNA or the autosomal chromosomes. We also find evidence for overall restricted introgression in the JAK/STAT signalling pathway. Echoing results in other species including humans, we find evidence for enhanced and/or directional introgression of immune‐related genes or pathways including the toll‐like receptor pathway, the blood coagulation pathway, and the LY96 gene. Finally we show enhanced introgression and excess chacma baboon ancestry in the sperm tail gene ODF2 . Together, our results elucidate the dynamics of introgressive hybridization in a primate system while identifying genes and pathways possibly under selection.